Inovasi Desain Pembelajaran Agama Islam Berbasis Konsep “Tringa” Ki Hadjar Dewantara dalam Meningkatkan Keterampilan Literasi - Hidayat, Mutik; Nafi’a, Muhammad Zidni Ilman (Journal of Management, Education and Communication, 2024)
This research examines the role of innovative Islamic learning design based on Ki Hadjar Dewantara's "Tringa" concept in improving literacy skills. The aim of this research is to develop a combined research method learning design using Ki Hadjar Dewantara's "Tringa" concept approach in an effort to increase students' interest in writing. By using a mixed research method, a mixed research method, namely combining qualitative and quantitative research methods, with the development model approach used being Dick and Carey. The research results show that: 1) according to experts, the feasibility test score obtained an average percentage of 90% which shows that the learning design is feasible, so that it can be continued to the trial stage with students. 2). Field trials carried out on students obtained an average percentage of 90%. Based on these results, it can be concluded that the developed learning design can improve students' literacy skills.